First principle calculation on the structural, electronic and transport properties of graphene, silicene and germanene substrate system - Hamid, Mohamad Amin (2020)
Although graphene, silicene and germanene are an interesting thin nanomaterial with various applications in novel electronic and spintronic devices, the zeroband-gap band structure limits the integration. By stacking different monolayer together, bandgap in graphene, silicene and germanene can be modulated by controlling the stacking configuration and interlayer distance. In this thesis, the structural, stabilities, electronic band, and electronic transport properties of graphene/silicene and graphene/germanene have been studied in three different stacking configurations, which is top, hollow, and bridge configurations using density functional theory and Boltzmann transport equation from first principle calculation. The computation for structural, stabilities and electronic band is performed by using Quantum ESPRESSO. Then, the output is utilized by BoltzTraP package to compute the electronic parts of transport properties for both graphene/silicene and graphene/germanene. This first principle study is motivated to contribute and further enriched the understanding of stacking effects in building two-dimensional superlattice materials. The results in this thesis can be divided into three part which are the structural, electronic and electronic transport properties per unit cell of graphene/silicene and graphene/germanene. The first part is the structural properties where graphene/silicene and graphene/germanene superlattice are modelled in top, hollow and bridge stacking configurations. Then, the initial structure of graphene/silicene and graphene/germanene is optimized. From the structural optimization, the structural changes experienced by graphene/silicene and graphene/germanene is tabulated in comparisons to pristine graphene, silicene and germanene. The interlayer binding energy and formation energy is computed to find the most stable stacking configurations. For both graphene/silicene and graphene/germanene, it is found that the most stable is top stacking configurations, followed by hollow and bridge stacking. The second part is the electronic properties of graphene/silicene and graphene/germanene. Here, the effect of stacking of the superlattices on the electronic band structure is studied. For both graphene/silicene and graphene/germanene, there is a bandgap opening at K-point with graphene/germanene displaying the self-hole doping characteristics. This study further delved into the effects of stacking configuration on the effective mass of graphene/silicene and graphene/germanene at K-point. Here, the effective mass of electrons is found to increased due to the bandgap opening at K -point. The effects of modulating the interlayer distance of graphene/silicene and graphene/germanene on the bandgap and the effective mass of electrons is also studied and found that decreasing the interlayer distance increased the bandgap and in returns increase the effective mass of electrons for both graphene/silicene and graphene/germanene. The electronic transport properties consist of electrical conductivity, electronic thermal conductivity and Seebeck coefficient of graphene/silicene and graphene/germanene. From the Seebeck coefficient, the majority charge carrier in both graphene/silicene and graphene/germanene is electrons making both of it n-type semiconductors. Generally, electrical conductivity, electronic thermal conductivity and Seebeck coefficient for both graphene/silicene and graphene/germanene is better in n-type doping region. However, an increase in n-type doping concentration induced bipolar transport properties in graphene/germanene which switch the polarity from n-type to p-type semiconductors.